Awake Nasal Fiberoptic Intubation in Diffuse Para-pharyngeal Abscess - Abdul Jabbar Ismail; Wan Aireene Wan Ahmeed; Rhendra Hardy Mohd Zaini; Wan Fadzlina Wan Muhd Shukeri; Mohd Zulfakar Mazlan (Egyptian Society of Ear Nose Throat and Allied Sciences, 2021)
This is a case report on awake fibreoptic intubation for a patient with a deep neck space infection. Intubation in this group of patients is considered difficult. It is challenging to anaesthesiologists, emergency physicians and otorhinolaryngologists because there is no consensus for airway management in these patients. We present a 30-year-old gentleman with swelling over the right cheek, difficulty breathing and severe trismus. He had a history of toothache one month prior to admission. Upon clinical examination, there was a diffuse swelling over the right mandible. Other examinations were unremarkable. Provisional diagnosis of a right para-pharyngeal abscess was made secondary to a possible infected right lower 3rd molar, with a differential diagnosis of a right parotid abscess with para-pharyngeal extension. Radiological assessment using computed tomography (CT) of the head and neck region showed an abscess over the right para-pharyngeal area, soft palate and right submandibular region. The narrowest part of the airway was at the region posterior to the soft palate, measuring approximately 1 cm. All staff and equipment were prepared for intubating a difficult airway. The patient was transferred to the control environment (operation theatre) for intubation. Awake nasal fibreoptic intubation (AFOI) was successfully performed for this patient using intravenous dexmedetomidine alone as the sedative.